Gamification and vocabulary learning among superior basic education students at a public institution in Loja city, school year 2023-2024 - Olmedo Troya, Paula Caroline (2024)
Vocabulary is considered the basis for the development of all other skills in any language; therefore, a good command and a large vocabulary will allow EFL students to understand the language and communicate smoothly. In this sense, the main objective of this research was to improve vocabulary learning through gamification, it was carried out among twenty-seven tenth grade students of a public institution in Loja during the school year 2023-2024. A mixed method based on action research was used, since the researcher used a pre-test and a post-test as instruments to collect quantitative information and evaluate the students' vocabulary knowledge and thus identify the effectiveness of gamification before and after the intervention plan, in addition a questionnaire was applied to collect qualitative data related to the students' perceptions about the use of gamification to improve their vocabulary learning. The data collected were interpreted using descriptive statistics and analyzed with thematic analysis. The results indicated that students improved their vocabulary learning in aspects such as use, meaning, spelling and pronunciation. Likewise, the results showed that students agreed that the use of gamification through gamified platforms such as Kahoot, Quizlet app and Wordwall.net and the implementation of game elements fostered positive engagement during classes, kept them motivated and allowed them to improve their vocabulary learning. Therefore, the researcher concluded that the participants perceived positively the use of gamification as it facilitates the process of memorizing new vocabulary and encourages students to work both collaboratively and individually generating motivation and a positive attitude towards learning. Keywords: Gamification; English vocabulary; learning process